HOTEL HIJAU SEBAGAI ALTERNATIF PENGURANGAN DAMPAK LINGKUNGAN - Nanny Roedji Roedji (Jurnal Pariwisata Pesona, 2016)
Nowadays, eviromental management has gotten a fully attention. Then, hospitality industry in East Java Province has committed to the Eco Friendly Enviroment needs a deep investigation in order to analyze a practical managment of hotel product which uses an eviromental friendly method in improving efficiency of energy, water, air quality, and solid waste management and liquid waste management system. This research used a descriptive qualitatif method which chracterized causuality and using a survey method. Data were collected by using an istitutional-perceptional approach and were analyzed by using enviromental performance scale from 1 to 5 point toward Green Hotel practice. The conclusion from the investigation result are; 45% hotel understand the concept and green product implementation. 50% hotel reuse the water to pour the garden. 40% about operating procedure such as towel reuse and bed sheet. 90% of the hotel already use VRV air-conditioner which can adjust the temperature suitable with the number of the people in the room and its automatically turn off when there are no people in the room. 45% shows that hotel provide dispenser to combine shampoo and conditioner (hair moisturizer) in one product so it will decrease the plastic waste.